Radiated energy fraction of SPI-induced disruptions at ASDEX Upgrade - P. Heinrich; G. Papp; S. Jachmich; J. Artola; M. Bernert; P. de Marné; M. Dibon; R. Dux; T. Eberl; J. Hobirk; M. Lehnen; T. Peherstorfer; et al. (Nuclear Fusion)
Future large tokamaks will operate at high plasma currents and high stored plasma energies. To ensure machine protection in case of a sudden loss of plasma confinement (major disruption), a large fraction of the magnetic and thermal energy must be radiated to reduce thermal loads. The disruption mitigation system for ITER is based on massive material injection in the form of shattered pellet injection (SPI). To support ITER, a versatile SPI system was installed at the tokamak ASDEX Upgrade (AUG). The AUG SPI features three independent pellet generation cells and guide tubes, and each was equipped with different shatter heads for the 2022 experimental campaign. We dedicated over 200 plasma discharges to the study of SPI plasma termination, and in this manuscript report on the results of bolometry (total radiation) analysis. We found, that the amount of neon inside the pellets is the dominant factor determining the radiated energy fraction ( $f_{rad}$ ). Large and fast fragments, produced by the ${12.5^{°}}$ rectangular shatter head, lead to somewhat higher values of $f_{rad}$ compared to the 25° circular or rectangular heads. This effect is strongest for neon content of $\lesssim3 × 10^{20}$ neon atoms ( $f_neon \lesssim 1.25%$ neon) injected, where a lower normal velocity component (larger fragments) seems slightly beneficial. While full-sized, 8 mm diameter, 100% deuterium ( $D_2$ ) pellets lead to a disruption, the 4 mm or shortened 8 mm pellets of 100% $D_2$ did not. The disruption threshold for 100% $D_2$ is found to be around $1 × 10^{22}$ deuterium molecules inside the pellet. While the radiated energy fraction of non-disruptive SPI is below 20%, this is increased to 40% during the thermal quench and vertical displacement event phase of the disruptive injections. For deuterium–neon-mix pellets, $f_{rad}$ -values of $\unicode{x2A7D}90$ % are observed, and the curve saturates around 80% already for 10% neon mixed into the 8 mm pellets ( $2 × 10^{21}$ neon atoms).